Poverty in Slovenia through the key themes in a life course approach - Živoder, Andreja (Annales. Series historia et sociologia, 2025)
In this paper we present results of a qualitative study on the life course and everyday life of poor elderly people in Slovenia. 33 in-depth biographical interviews were conducted with individuals aged 65 and over living in poverty. By examining empirical data through the lens of the key themes of the life course approach, the aim of the article is to illuminate the intricate ways in which poverty unfolds and develops over time, in different periods of life as well as different in life trajectories, such as education, employment, family and health trajectory
Keywords: cumulative poverty; družbeni in zgodovinski kontekst; kumulativna revščina; life course; linked lives; old people; poverty; povezana življenja; prehod; Revščina; social an historical context; stari ljudje; Starostniki; transition; življenjski potek